Home - Smith, Alex T. (London : Scholastic Children's Books, 2013)
Four best friends begin to understand the meaning of home after going their separate ways.
Cover title: Once there was a house, a house that was a-- home.
2.9
K-3.
K-3
Keywords: Friendship -- Juvenile fiction; Home -- Juvenile fiction; Friendship -- Fiction; Home -- Fiction; Friendship -- Fiction; Home -- Fiction; Picture books for children